Research and Experience in an Artist-in-Residence Program: The ÁHQIS Acting Laboratory in Fortaleza (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This material documents the artistic residency conducted by the ÁHQIS Acting Laboratory at the Carlos Câmara Theatre (Fortaleza) as an experience that integrates practice-based research, pedagogical processes, and University Extension. The text, together with the accompanying photographic dossier, records performances, staged readings, workshops, and lectures, offering a reflection on research as the guiding principle of an educational experience developed within the framework of an academic research group.
Keywords: acting; theater of Intensities; creative practice as research; pedagogical experience